Implementasi Pendidikan Multikultural dalam Pendidikan Agama Islam Di Sekolah - Nadiyah Nadiyah (Program Studi PAI STAI Al Falah Banjarbaru, 2026)
Multicultural education in a pesantren-based school should be understood not merely as recognition of diversity, but as an educational process embedded in the curriculum, learning practices, and patterns of interaction among students. This study analyzes the implementation of multicultural education in Islamic Religious Education (PAI) at Darul Hijrah Junior High School, focusing on Muthola’ah learning. The study employed a qualitative descriptive approach and purposive sampling. Participants included the principal, teachers, and student representatives from each class involved in the learning activities. Data were collected through interviews, observation, and documentation and analyzed descriptively and inductively. Data credibility was strengthened through source and technique triangulation by comparing information from different participants and checking it against observation and documentation. The findings indicate that multicultural practices are reflected in mutual respect, deliberation, togetherness, cooperation, and helping one another. Muthola’ah provides an important learning space because stories and moral messages are not treated merely as textual material, but are processed through discussion and presentation. The teacher also connects the material with Qur’an-Hadith and Akidah Akhlak, giving moral messages a religious context and directing them toward everyday application. From a constructivist perspective, the process demonstrates that students construct understanding through experience, interaction, exchange of ideas, and reflection. Thus, multicultural education at Darul Hijrah operates primarily through learning experiences that allow students to express opinions, listen to different perspectives, and develop shared understanding.